Peachie Peachie wrote:
AvidDreamer09 wrote:
Formula to remember for this question \(= a^2-b^2 = (a+b)(a-b)\)
\(\frac{√3−2}{√2+1}*\frac{√2-1}{√2-1}=\frac{(√3−2)(√2-1)}{2-1}=(√3−2)(√2-1)\)
\((√3−2)(√2-1) =√2√3-√3-2√2+2=P\)
\(P-4 = √2√3-√3-2√2+2-4 = √6-√3-2√2-2 =−2√2+√6–√3–2\) (with a little rearranging you get D)
WHERE DID YOU GET
√2−1√2−1 From??? Confused
Posted from my mobile deviceSo what i did was multiplied (√2−1) to the numerator and denominator.... this does not change the equation but it helps to simplify the equation...
As a rule of thumb try eliminating the denominator when you get questions like these